The Effect of Liquid Application Times, and Mixer Types with Different Wet Mix Times on Uniformity of Mix - M. Saensukjaroenphon; C. K. Jones; C. H. Fahrenholz; C. R. Stark (Kansas Agricultural Experiment Station Research Reports, 2016)
Liquid addition systems are often designed to add liquid ingredients with the shortest application time in order to increase the batching capacity and efficiency of the mixing process. The quantity of liquid that is added into the mixer affects batch cycle time, particularly when there is a programmed “wet mix” time, or mixing time after liquid application has completed. Shorter application time of liquids typically produces a larger droplet size, which may lead to greater clumping tendencies in the feed and less uniformity of liquid incorporation. Two experiments were conducted to determine the effect of liquid application time and wet mix time on the uniformity of mix in different mixers. In both experiments, treatments were arranged in a 2 × 3 factorial. Experiment 1 used a double ribbon mixer with 2 liquid application times (20 vs. 30 s) and 3 wet mix times (15, 30, and 45 s). Experiment 2 used a single shaft paddle mixer with 2 liquid addition times (15 vs. 30 s) and 3 wet mix times (15, 30 and 45 s). Ten samples were collected, and coefficient of variation (% CV) determined within those samples. Each treatment had 10 separate replicates. Experiment 1 indicated that wet mix time (P<0.0001), but not application time (P = 0.653) or the interaction (P = 0.638), impacted % CV in the double ribbon mixer. As wet mix time increased, % CV decreased in a quadratic manner (P = 0.02; 37.2, 18.6, and 10.8% for 15, 30, and 45 s wet mix time, respectively). In Experiment 2, both wet mix time (P = 0.030) and application time (P = 0.001) impacted % CV, but not their interaction (P = 0.290). A longer application time led to a better uniformity of mix (P<0.05; 13.5 vs. 9.8% CV for 15 vs. 30 s liquid application time), as did a longer wet mix time (P<0.05; 17.0, 9.8, and 8.2% CV for 10, 20, and 30 s wet mix time, respectively). These results suggest that extending liquid application times may be beneficial in some mixers, and underscore the importance of a sufficient wet mix time to maximize the uniformity of liquid incorporation.
Keywords: liquid addition; wet mix; uniformity of mix